-3p+7=6-10p-5

Simple and best practice solution for -3p+7=6-10p-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3p+7=6-10p-5 equation:


Simplifying
-3p + 7 = 6 + -10p + -5

Reorder the terms:
7 + -3p = 6 + -10p + -5

Reorder the terms:
7 + -3p = 6 + -5 + -10p

Combine like terms: 6 + -5 = 1
7 + -3p = 1 + -10p

Solving
7 + -3p = 1 + -10p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '10p' to each side of the equation.
7 + -3p + 10p = 1 + -10p + 10p

Combine like terms: -3p + 10p = 7p
7 + 7p = 1 + -10p + 10p

Combine like terms: -10p + 10p = 0
7 + 7p = 1 + 0
7 + 7p = 1

Add '-7' to each side of the equation.
7 + -7 + 7p = 1 + -7

Combine like terms: 7 + -7 = 0
0 + 7p = 1 + -7
7p = 1 + -7

Combine like terms: 1 + -7 = -6
7p = -6

Divide each side by '7'.
p = -0.8571428571

Simplifying
p = -0.8571428571

See similar equations:

| 9x+7=3x-9 | | 2r-6r=12 | | -(c-12c-c-3c)= | | 4(b+3)=24 | | -18-6k=6(p-8) | | x(3x+11)=20 | | 12+z-x= | | 6m^3n^3*8m^2n^3= | | 4b+2=6b-6 | | (8-3(1))= | | 2X+8+3X= | | -56=4-5x | | 7(x-2)+2(x+4)+27=180 | | -14b+28=-10b+30 | | 13m=11 | | 6x+5=-7+4x+24 | | 6x^4=5 | | x.x-x=2x-2 | | 1+4n+1=-18 | | 7x^4+9x^3-41x^2-13x+6=0 | | x^2=-8+6x | | 8-5(x+1)=9+x | | 6(2x+4)=4(3x+6) | | 14-(2q+5)=-29+9 | | 72=-12m | | 12a^5-6a^2= | | 2(x+3)+4x-3=5x+12 | | 1.5(x-2.5)=3 | | 10x-4=56 | | .25j+8=20 | | 2n+(2n+4)=6 | | 5x^3-15x^2= |

Equations solver categories